2167. Use and Timing of Antiviral Therapy for Influenza in Hospitalized U.S. Children, 2016–2020. (15th December 2022) - Amarin, Justin Z; Stewart, Laura S; Potter, Molly; Spieker, Andrew J; Chappell, James; Williams, John; Boom, Julie A; Englund, Janet A; Selvarangan, Rangaraj; Schuster, Jennifer E; Staat, Mary A; Weinberg, Geoffrey A; et al.
Abstract: Background: According to the 2018 Infectious Diseases Society of America (IDSA) clinical practice guidelines and Centers for Disease Control and Prevention (CDC) guidance, clinicians should start antiviral treatment as soon as possible for children who are hospitalized with suspected or confirmed influenza. We assessed the use of influenza-specific antiviral therapy in children hospitalized with symptoms of acute respiratory illness and laboratory-confirmed influenza. Methods: We conducted active, population-based surveillance of children hospitalized with fever and/or respiratory symptoms (12/01/2016–02/28/2020) at the seven U.S. medical centers that comprise the CDC New Vaccine Surveillance Network. We excluded children who did not undergo clinical testing (by rapid antigen testing or nucleic acid amplification test [NAAT]) or research testing (by NAAT) for influenza, those who presented out of influenza season (site- and season-specific), and those whose date of antiviral therapy or whether antiviral therapy was given was unknown. We assessed the use of influenza-specific antiviral therapy in this cohort and defined timely antiviral therapy as administration within 2 days of hospitalization. Results: Of 11, 275 eligible children, 1, 149 (10.2%) tested positive for influenza by clinical and/or research assays (Table 1 ). Overall, 154 influenza cases (13.4%) were detected by clinical testing only, 428 (37.2%) by research testing only, and 567 (49.3%) by both. During their influenza-associated hospitalization, 620 children (54.0%) received influenza-specific antivirals, and therapy was timely in 572 cases (92.3%). Of those who tested positive clinically, 445/721 (61.7%) received timely antiviral therapy, 38 (5.3%) received delayed antiviral therapy, and 238 (33.0%) received no antiviral therapy. Oseltamivir was the antiviral used in all treated cases. The distribution of antiviral-treated cases varied by race and Hispanic origin and study site, but not by age at presentation or influenza season (Figure 1 ). Table 1 Demographic characteristics of 1, 149 children with influenza enrolled in the New Vaccine Surveillance Network over four influenza seasons between December 1, 2016, and February 28, 2020. Figure 1 Proportions of children with influenza enrolled in the New Vaccine Surveillance Network who received timely, delayed, or no antiviral therapy by age at presentation, race and Hispanic origin, study site, and influenza season (N=1, 149). Conclusion: Although antiviral therapy is recommended for all influenza-associated hospitalizations in children, antiviral prescribing remains suboptimal. Further studies would help identify and address barriers to antiviral therapy in children with influenza. Disclosures: John Williams, MD, GlaxoSmithKline: Advisor/Consultant|Quidel: Advisor/Consultant Janet A. Englund, MD, AstraZeneca: Advisor/Consultant|AstraZeneca: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Meissa Vaccines: Advisor/Consultant|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support Mary A. Staat, MD, MPH, Centers for Disease Control and Prevention: Grant/Research Support|Cepheid: Grant/Research Support|National Institute of Health: Grant/Research Support|Uptodate: Royalties Geoffrey A. Weinberg, MD, Merck & Co.: Honoraria|Merck & Co.: Honoraria for composing and reviewing textbook chapters, Merck Manual of Therapeutics Flor M. Munoz, MD, MSc, Gilead: Grant/Research Support|Moderna: DSMB|Pfizer: DSMB Christopher J Harrison, MD, Astellas: Grant/Research Support|GSK: Grant/Research Support|Merck: Grant/Research Support|Pediatric news: Honoraria|Pfizer: Grant/Research Support Natasha B. Halasa, MD, Quidel: Grant/Research Support|Quidel: equipment donation|Sanofi: Grant/Research Support|Sanofi: HAI testing and vaccine donation.